The English Capital Market - Lavington, Frederick (London, Cass, 1968)
This book attempts to trace the nature of the economies which the market effects as part of the organization of production, and to express those economies in terms of economic welfare.
Originally published 1921.
Bibliographical references included in "Notes" (p. 283-294)
osc 12/06/17
Loans
Keywords: Finance; Banks and banking; Capital; Investments